Two consecutive heterogeneous reactions of second order in well mixed aerosol system - Kopiychenko, D.Yu.; Mchedlov-Petrossyan, P.O.; Khomenko, G.A. (Вопросы атомной науки и техники, 2007)
The dynamics of concentration changes in well-mixed systems with two consecutive heterogeneous reactions of the second order on the surface of monodisperse aerosol particles is analyzed in the case of mass transfer limitations. A self-consistent set of equations is proposed. All possible variants of concentration changes were classified. Initial concentrations and mass transfer coefficients which lead to these variants were determined. It is shown that number of possible switches increases from one in the case of one binary reaction to three for consecutive reactions of the second order.